Tentative key to robber fly (Diptera: Asilidae) subfamilies based on pupal cases - Dennis, D. Steve; Barnes, Jeffrey K. (Zootaxa, 2011)
Subfamily keys for pupal cases of Asilidae are currently based on 5 taxa, Asilinae, Dasypogoninae, Megapodinae, Laphriinae and Leptogastrinae. Analysis of recently published adult morphological data and DNA sequence data suggests that the family consists of 14 subfamilies. A tentative key based on known pupal cases is provided for 10 of these subfamilies: Asilinae, Brachyrhopalinae, Dasypogoninae, Dioctriinae, Laphriinae, Leptogastrinae, Ommatiinae, Stenopogoninae, Stichopogoninae and Willistonininae. It is difficult to distinguish between Brachyrhopalinae and Dasypogoninae pupal cases because so many characteristics overlap. There are no described pupal cases for 4 subfamilies: Bathypogoninae, Phellinae, Tillobromatinae and Trigonomiminae. Morphological data are available for only approximately 10% of the genera and 2% of the species of Asilidae.